1999
DOI: 10.1897/1551-5028(1999)018<0708:ciitst>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibition in Tree Swallows (Tachycineta Bicolor) and Eastern Bluebirds (Sialia Sialis) Exposed to Organophosphorus Insecticides in Apple Orchards in Ontario, Canada

Abstract: Abstract-Apple orchards occupy approximately 12,565 ha of land in Ontario, Canada, and are treated with the greatest number and applications of pesticides among all agricultural crops within the province. The potential for exposure to wildlife from frequent organophosphorus (OP) spray applications is therefore considerable. This study investigated the impact of agricultural spray applications of azinphos-methyl, diazinon, phosalone, and phosmet in apple orchards on the cholinesterase (ChE) activity of wild bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Nizam (1993) reported 49% and 57% inhibition of AchE after Nfb and nimocinol treatment in subject animal. Burgees et al (1999) observed that organophosphate decreased cholinesterase activity in birds and these insecticide also produced tremors loss of Table 3. Activity of cholinesterase in brain of Rana cyanophyctis treated with lambda cyhalothrin 65.9 muscular control and paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nizam (1993) reported 49% and 57% inhibition of AchE after Nfb and nimocinol treatment in subject animal. Burgees et al (1999) observed that organophosphate decreased cholinesterase activity in birds and these insecticide also produced tremors loss of Table 3. Activity of cholinesterase in brain of Rana cyanophyctis treated with lambda cyhalothrin 65.9 muscular control and paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…A classical biomarker of exposure to OP or CA is the inhibition of cholinesterase (ChE) activity. This biomarker was successfully applied to birds in apple orchards [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These environments present complex exposure scenarios for birds because orchards receive multiple pesticides per application and multiple applications per season. Additionally, orchards attract many species of birds because they provide habitat for nesting and other resources (Bishop et al 2000;Boutin et al 1999;Bouvier et al 2011;Burgess et al 1999;Fluetsch and Sparling 1994;Johnson et al 1976;Wilson et al 2001). Anti-ChE insecticides, which inhibit acetylcholinesterase, are still used in these and other agricultural environments, and because of their toxicity and nonselective mode of action, adverse effects have been observed over a wide taxonomic spectrum, including birds (e.g., Elliott et al 2008;Gill et al 2004;Parsons et al 2010;Strum et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, little empirical data or guidance exists for choosing indicator species for contaminant studies with labile chemicals that have the potential for short-term but highly acute effects (Greig-Smith 1990). Indicator species used in field studies with pesticides are often selected on the basis of abundance and convenience in collecting data with that species (e.g., Millikin and Smith 1990; see also Bouvier et al 2005;Burgess et al 1999;Greig-Smith 1990;Jones 2003;Patnode and White 1991;Rondeau and DesGranges 1995). Selection of a species based on its abundance may provide greater numbers of individuals for study and analysis, but a species may be abundant because it is less sensitive or does not receive the exposure necessary to result in a toxic effect.…”
Section: Introductionmentioning
confidence: 99%